Introduction to the Hebrew Bible: and deutero-canonical books - Collins, John J. (Fortress Press, 2014)
Introduction to the Hebrew Bible is one of the most reliable and widely adopted critical textbooks at undergraduate and graduate levels alike. The text is aimed explicitly at motivated students regardless of their previous exposure to the Bible or faith commitments. Collins proceeds through the canon of the Old Testament and the Apocrypha, judiciously presenting the current state of historical, archaeological, and literary understanding of the biblical text, and engaging the student in questions of significance and interpretation for the contemporary world. The revised second edition is now presented in a refreshing new format